1999
DOI: 10.1046/j.1365-2664.1999.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding success and causes of breeding failure of curlew Numenius arquata in Northern Ireland

Abstract: Summary 0[ The present study investigated breeding success and causes of breeding failure of curlew\ a species for which the UK holds internationally important breeding numbers[ Studies were undertaken between 0882 and 0884 in two areas of Northern Ireland\ where the species| breeding range has recently contracted and breeding numbers are declining[ Avian nest predators were abundant in both areas\ whereas foxes were abundant on the Antrim study area but generally were absent from the Lough Erne study area\ wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
107
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 36 publications
6
107
1
2
Order By: Relevance
“…There is broad agreement that this reduced breeding productivity is caused primarily by agricultural intensification, leading to an increase in direct clutch and chick mortality and to food availability problems (Beintema et al 1997;Vickery et al 2001;Wilson et al 2004;Schekkerman and Beintema 2007). However, concerns have also been raised that predation causes population declines or precludes recovery in response to conservation measures (Grant et al 1999;Langgemach and Bellebaum 2005;Bolton et al 2007). A complicating factor in the ensuing discussions about conservation strategies is the possibility that predation eliminates mainly prey with already reduced survival prospects (Swennen 1989) or interacts with agricultural land use (Evans 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is broad agreement that this reduced breeding productivity is caused primarily by agricultural intensification, leading to an increase in direct clutch and chick mortality and to food availability problems (Beintema et al 1997;Vickery et al 2001;Wilson et al 2004;Schekkerman and Beintema 2007). However, concerns have also been raised that predation causes population declines or precludes recovery in response to conservation measures (Grant et al 1999;Langgemach and Bellebaum 2005;Bolton et al 2007). A complicating factor in the ensuing discussions about conservation strategies is the possibility that predation eliminates mainly prey with already reduced survival prospects (Swennen 1989) or interacts with agricultural land use (Evans 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Radio-tagging has been used to study chick mortality in ducks (Korschgen et al 1996;Pietz et al 2003), gamebirds (Riley et al 1998;Larson et al 2001), bustards (Combreau et al 2002) and shorebirds (Miller and Knopf 1993;Grant et al 1999;PearceHiggins and Yalden 2003;Ratcliffe et al 2005;Bolton et al 2007). A potential drawback of radio-tagging is that the transmitters may affect the chicks' behaviour or physiology and reduce their survival prospects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Red Grouse, Rock Ptarmigan Lagopus muta respond adversely to louping ill virus infections (Reid et al 1980), but it is not known whether other ground-nesting birds and their chicks are affected by high tick abundance or if they are susceptible to tick-borne diseases. Chicks of moorland breeding waders can host ticks, indeed high tick infestations have been cited as the cause of death for Curlew chicks (Grant et al 1999) and a single Curlew chick has tested seropositive for louping ill virus (D. Newborn, pers. comm.…”
mentioning
confidence: 99%
“…This analysis was also hampered by the fact that low breeding success reduced the sample size of wader chicks, particularly among Curlews, from which tick burdens and body condition could be recorded. Previous work has associated high tick burdens with the death of Curlew chicks (Grant et al 1999) although the presence of tick-borne diseases were not investigated.…”
mentioning
confidence: 99%
“…To date, there have been few studies on the effects of habitat fragmentation on nest predation rates of ground-nesting birds in open habitats (Andrén 1995). In such habitats, waders (Charadrii) often suffer high nest-losses due to predation (Beintema & Müskens 1987, Baines 1990, Berg 1992, and some studies have suggested nest predation as the major cause of population declines of breeding wader populations (Jönsson 1991, Grant et al 1999, Jackson & Green 2000. In some cases, predation risk of wader nests has been related to indirect measures of fragmentation, such as proximity to forest edge or other potential lookouts for avian predators (Berg et al 1992a).…”
mentioning
confidence: 99%